The U.S. balance of payments: freedom or controls - HABERLER, G. (PSL Quarterly Review, 2014)
In the last two years the U.S. balance of payments and the international position of the dollar have undergone sharp and somewhat paradoxical changes. Despite the unprecedented deterioration of the external balance in 1969, the dollar was left entirely unscathed in the exchange market. The article considers this paradox, the dollar’s position as the world’s foremost reserve currency and flexibility with regards to exchange rate adjustment. The author argues that the real choice is not between fixed exchange rates and some sort of flexibility, but rather between a messy and disorderly method of changing exchange rates that entails crisis, speculation and controls, and a smooth adjustment which largely avoids controls and reduces speculation to a minimum. JEL: F32, E42